Voting and Nonlinear Taxes in a Stylized Representative Democracy - Henning Bohn; Charles Stuart (Center for Economic Studies and ifo Institute (CESifo), 2003)
We derive median-voter results and study the shape of redistributional taxes when voters elect a candidate who imposes taxes to maximize own utility. Under general conditions, a median-productivity candidate is a Condorcet winner. The imposed tax function is nonlinear, may place high marginal rates on very low incomes, and may have an interval of negative marginal rates below the income of the winning candidate. Marginal rates are positive throughout, however, if non-redistributional spending or altruism toward the poor are great enough.
Keywords: 330